Designing Balance into the Democratic Project: Contrasting Jeffersonian Democracy against Bentham's Panopticon Centralisation in determining ICT adoption - Kakabadse, Nada K.; Kakabadse, Andrew P.; Kouzmin, Alexander (Cranfield University, 2007)
Positioned in a critical realist perspective, this paper examines the impact of systematic and institutional distortion to communication and the use of information and communicative technology (ICT) for control over citizen participation within the Liberal-democratic process. The paper contrasts the Jeffersonian vision of democracy against Bentham’s Panopticon dystopia and reviews comparative models of democratic processes. In so doing, it is argued that the role of ICT, the role of pressure groups and concentrated media ownership and control pose significant issues for E-democracy, in particular that of less unfettered communication within the context of Liberal democracy. It is concluded that a new constitutional organ is required to enhance genuine participation within the Panopticon proclivities emergent in E-democrac
Keywords: Citizen; Communication; Democracy; E-democracy; Governance; Information; Jeffersonian Vision; Lobby Groups; Bentham’s Panopticon; Public Policy